2021
DOI: 10.1038/s41419-021-04184-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPK agonist alleviate renal tubulointerstitial fibrosis via activating mitophagy in high fat and streptozotocin induced diabetic mice

Abstract: Renal tubulointerstitial fibrosis was a crucial pathological feature of diabetic nephropathy (DN), and renal tubular injury might associate with abnormal mitophagy. In this study, we investigated the effects and molecular mechanisms of AMPK agonist metformin on mitophagy and cellular injury in renal tubular cell under diabetic condition. The high fat diet (HFD) and streptozotocin (STZ)-induced type 2 diabetic mice model and HK-2 cells were used in this study. Metformin was administered in the drinking water (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 41 publications
2
82
0
Order By: Relevance
“…Metformin can act on NF-κB signaling, inhibit monocyte to macrophage differentiation, and suppress several pro-inflammatory cytokines in the plasma of non-diabetic patients ( Isoda et al., 2006 ). Furthermore, metformin ameliorated renal oxidative stress and tubulointerstitial fibrosis in DKD mice by activating mitophagy through Pink1 (PTEN-induced putative kinase 1) and Parkin ( Han et al., 2021 ).…”
Section: Dkd Therapy Targeting Oxidative Stress and Mitochondrial Fun...mentioning
confidence: 99%
“…Metformin can act on NF-κB signaling, inhibit monocyte to macrophage differentiation, and suppress several pro-inflammatory cytokines in the plasma of non-diabetic patients ( Isoda et al., 2006 ). Furthermore, metformin ameliorated renal oxidative stress and tubulointerstitial fibrosis in DKD mice by activating mitophagy through Pink1 (PTEN-induced putative kinase 1) and Parkin ( Han et al., 2021 ).…”
Section: Dkd Therapy Targeting Oxidative Stress and Mitochondrial Fun...mentioning
confidence: 99%
“…It has been shown that treatment with metformin, as an AMPK agonist, can well moderate mitophagia in epithelial cells of the proximal tubule of the kidney (Zhao and Sun 2020 ). In addition, Ya-chun Han et al Also showed that the use of metformin could decrease the risk of fibrosis in the renal interstitial tube associated with mitophage activation via the AMPK-Pink1-Parkin pathway (Han et al 2021 ). Another study showed that the use of metformin in renal nephrectomy models following renal disease could halt the progression of chronic renal disease, including renal fibrosis, and that activation of AMPK may contribute to the protective effect of metformin nephroprotechnics (Borges et al 2020 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…As known, mitochondria mainly provide ATP and energy to maintain cellular homeostasis and regulate the communication between cells and tissues. Recent studies showed that mitochondria play an important role in HFD-induced renal inflammatory injury ( Sun et al, 2020 ; Han et al, 2021 ; Lubojemska et al, 2021 ). Mitochondrial dysfunction-induced by HFD is related to mitochondrial fatty acid oxidative (FAO) impairment, dynamic change (e.g., mitochondrial fission and fusion) and mitophagy deficiency.…”
Section: Hfd-induced Renal Tubular Inflammatory Injury and Its Potential Underlying Mechanismsmentioning
confidence: 99%
“…For the molecular mechanisms involved in this progress, Unc-51-like autophagy activating kinase 1 (ULK1) has been confirmed to be inactivated in HFD-induced renal injury ( Declèves et al, 2011 , 2014 ; Sohn et al, 2017 ; Luo et al, 2019 ). More important, the recovery of mitophagy deficiency can attenuate HFD-induced renal tubular inflammatory injury ( Han et al, 2021 ). In addition, mitochondrial dynamic changes were also reported in HFD ( Chen et al, 2018 ; Sun et al, 2020 ).…”
Section: Hfd-induced Renal Tubular Inflammatory Injury and Its Potential Underlying Mechanismsmentioning
confidence: 99%